Cardiovascular Drug Use and Risk of Actinic Keratosis: A Case-Control Study - Olga Warszawik-Hendzel; Małgorzata Olszewska; Adriana Rakowska; Mariusz Sikora; Piotr Hendzel; Lidia Rudnicka (Adis, Springer Healthcare, 2020)
Abstract Introduction Actinic keratosis (AK) is a precancerous skin lesion. Currently, many experts treat actinic keratosis as squamous cell carcinoma in situ. It is well established that exposure of the skin to ultraviolet radiation is a major risk factor for the development of actinic keratosis. Some studies suggest an association between keratinocyte cancers and photosensitizing cardiovascular drugs. The aim of this study was to establish an association between cardiovascular drug use and the presence of AK. Methods A total of 400 patients were enrolled into the study (200 with AK; 200 healthy persons in the control group). The group of patients with AK consisted of 106 women and 94 men (mean age 71 years). The control group included 102 women and 98 men (mean age 69 years). An analysis of the risk factors for developing actinic keratosis was performed in all patients with AK on the basis of a detailed, standardized interview. Results The statistical analysis showed that features independently associated with increased risk of AK included: age > 80 years (OR 4.14; 95% CI 2.4-7.3), positive cancer history (OR 1.94; 95% CI 1.0-3.6), positive history of sunburns when < 18 years old (OR 2.18; 95% CI 1.3-3.7) and taking angiotensin-converting enzyme inhibitors (OR 2.28; 95% CI 1.2-4.3), angiotensin receptor AT1 blockers (OR 2.90; 95% CI 1.1-7.9) and calcium channel blockers (OR 2.4; 95% CI 1.0-5.3). Conclusion In conclusion, our study presented an association between cardiovascular drug use and the risk of developing AK.